The precambrian geology of an area between Messina and Tshipise Limpopo mobile belt - Horrocks, Peter Charles Brammer (My University, 2015)
An area of about 200 'sq km has been mapped at a scale of 1 : 25 000 between Messina and Tshipise. Subsequent laboratory work has included petrographic, whole-rock and mineral analysis in order to describe the Precambrian rock-types and lithologies, their structure, and their metomorphic history. The Precambrian lithologies underlying the study area consist of grey banded basement gneisses of granodioritic composition, together with a large variety of supracrustal rocktypes. These include quartzo-feldspathic gneiss, Singeleletype granitoid gneiss, garnet-cordierite-sillimunite gneiss, sapphirine-bearing rock, garnet-orthopyroxene-plagioclase symplectite, pyroxenitic amphibolite, quartzite, banded magnetite quartzite, amphibolite, calc-silicate gneiss and marble. These supracrustal rocks may belong to a geosynclinal-type series of depv .» Led or extruded lithologies. Intrusive rocks of the Messina Layered Intrusion consist of gabbroic and anorthositic gneiss. Metapyroxenites and serpentinites also occur. Both ancient deformed and you ger fabric-free mafic dykes transect this stratigraphy. Polyphase deformation has produced complex and intense folding of the area. Early isoclinal and ductile folds, now manifest as tight intrafolial folds, have been refolded around later structures. Most fold hinges plunge moderately to the south-west. Considerable flattening, attenuation and alongstrike boudinaging of the units occurs in the region, probably as a result of regional simple shear The assymetry of the folds in the region suggest that this simple shear was left lateral. Peorce-type variation diagrams for data from the Messina Layered Intrusion show plagioclase fractionation trends, and support the argument that these rocks are of plutonic igneous origin. The anorthcsites were the earliest cumulates, with the gabbros forming by subsequent fractionation. Rayleigh's law indicates that about 70 per cent fractionation has occurred in these rocks. The parental liquid appears to have been anomalously enriched in rubidium. The supracrustal units have experienced a high-grade metamorphism between about 3 100 m.y. ago and 2 400 m.y. ago. The P-T conditions for this metamorphism range from about 9 kbar and 900 C at the 'peak' of the metamorphism, to about 4 kbar and 650°C, and thus represents a retrogression within the field of medium pressure granulites. Earlier high-pressure granulite metamorphism is indicated by assemblages reported from other regions in t.ie Central Zone of the Limpopo Mobile Belt. These data suggest that the supracrustal rocks were subjected to burial into regions of the lower crust up to 40 km depth, and geothermal gradients between 15°C/km and 35°C/km were experienced. Water activities were low durin.j this high-grade metoeorphism, with water making up not more than 10 per cent of the fluid present during this event. The onset of relative tectonic stability and the end of high-grade metamorphism was achieved by about 2 200 m.y. 0go.
A Dissertation Submitted tc the Faculty of Science, University of the Witwatersrand, Johannesburg, for the degree of Doctor of Philosophy. Johannesburg 1981
Keywords: Geology, Strati graphic--Precambrian